Ketogenic Diet Improves Sleep Quality and Daytime Sleepiness in Chronic Migraine: A Pilot Study - Yan Tereshko; Simone Dal Bello; Enrico Belgrado; Cherubino Di Lorenzo; Alice Pittino; Francesca Filippi; Francesca Valdemarin; Christian Lettieri; Gian Luigi Gigli; Annacarmen Nilo; Gaia Pellitteri; Giovanni Merlino; et al. (Neurology International)
Aims: The aim of this study is to assess the sleep quality and daytime sleepiness improvement in chronic migraineurs after 6 months of a 2:1 KD (ketogenic diet) and LGID (low-glycemic-index diet). Methods: Twenty-six patients underwent 2:1 KD (11 patients) and LGID (15 patients). PSQI (Pittsburgh sleep quality index) and ESS (Epworth sleepiness scale) were administered at the baseline and the 3-month and 6-month follow-up. MIDAS (Migraine Disability Assessment), HIT-6 (Headache Impact Test 6), migraine frequency (migraine days per month), migraine intensity, BMI (Body Mass Index), FM (Fat Mass), and FFM (Fat-Free Mass) were also assessed. Results: PSQI (F1.544, 38.606 = 7.250; p = 0.004), ESS (F1.988, 49.708 = 9.938; p < 0.001), HIT-6 (F1.432, 35.805 = 12.693; p < 0.001), migraine frequency (F1.522, 38.041 = 23.070; p < 0.001), migraine intensity (F1.949, 48.721 = 18.798; p < 0.001), BMI (F1.274, 31.857 = 38.191; p < 0.001), and FM (F1.245, 31.134 = 45.487; p < 0.001) improved significantly. The MIDAS (F1.005, 25.121 = 3.037; p = 0.093) and the FMM (F1.311, 32.784 = 1.741; p = 0.197) did not improve significantly. The ESS (p = 0.712) and PSQI (p = 0.776) data at 3-month and 6-month follow-ups did not differ significantly, as well as for migraine frequency, migraine intensity, BMI, FM, and HIT-6. A mild correlation emerged between the mean FM and mean ESS reduction during the 6 months (r = 0.497, p = 0.010). Conclusions: Six months of LGID and 2:1 KD can improve sleep quality and daytime sleepiness in patients with chronic migraine. The effectiveness on migraine, sleep quality, and daytime sleepiness does not differ significantly between the 3-month and 6-month follow-up periods.